On the masked mycotoxin zearalenone-14-glucoside. Does the mask truly hide?. (1st March 2016) - Dellafiora, Luca; Perotti, Alessio; Galaverna, Gianni; Buschini, Annamaria; Dall'Asta, Chiara
Abstract: In the matter of foodborne mycotoxins, beside a number of regulated compounds, regulations are totally missing for phase-II plant metabolites – the toxicological knowledge of which is still in its infancy. Currently, zearalenone-14-glucoside is in the pipeline and its toxicological role is under a glowing scientific debate. In our work it clearly showed high toxicological concerns as it is prone to conversion to well-known toxic compounds (i.e. zearalenone and both zearalenol isomers) when exposed to breast cancer cells culture. The need of future risk assessment studies has been pointed out accordingly. Graphical abstract: Highlights: ZEN-14-Glc is cleaved in breast cancer cell culture to release the parent form. Besides deglycosilation, ZEN-14-Glc biotransformation may occur in MCF7 cells as well. The xenoestrogenic activity of masked ZEN is not quenched by glucosilation.